Hovering rotor solutions by high-order methods on unstructured grids - Ricci, Francesco; Silva, Paulo A. S. F.; Tsoutsanis, Panagiotis; Antoniadis, Antonis F. (Elsevier, 2019)
This paper concerns the implementation and evaluation of high-order reconstruction schemes for predicting three well established hovering rotor flows i.e. Caradonna and Tung, PSP and UH-60A. Monotone Upstream Centred Scheme for Conservation Laws (MUSCL) and Weighted Essentially Non-Oscillatory (WENO) spatial discretisation schemes, up to fourth-order, are employed to approximate the compressible Reynolds Averaged Navier-Stokes (RANS) equations in a rotating reference frame, on mixed-element unstructured grids. Various flow speed conditions are simulated including subsonic and transonic, with the latter stretching the discontinuities capturing abilities of the numerics. We consistently evaluate the accuracy, cost and robustness of the developed numerical framework by analysing the discretisation error with respect to the grid resolution. A thorough validation is conducted for all cases by comparing the obtained numerical solutions with experimental data points and relevant literature
Keywords: High-order methods; CFD; MUSCL; WENO; Unstructured hybrid mesh; Rotorcraft